Pengaruh Media Cerpen Terhadap Kemampuan Membaca Pemahaman Siswa: The Influence of Short Story Media on Students' Reading Comprehension Ability - Azahra, Zelma; Kusumawati, Tri Indah (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study investigates the influence of short stories (cerpen) as a learning medium on students’ reading comprehension skills. The research was conducted at SDN 105362 Lubuk Dendang, with 20 fifth-grade students participating. Reading comprehension remains a significant challenge in the Indonesian education system, underscoring the need for effective strategies to enhance student learning outcomes. The primary objective of this study is to examine the effectiveness of short stories as an instructional tool in enhancing elementary students’ reading comprehension. Addressing the lack of practical and engaging teaching media, this study explores the role of short stories in fostering students’ understanding of texts. Using a quantitative research design with a one-group pretest–posttest approach, students’ reading comprehension was assessed before and after the intervention. The results show a significant improvement: the average pretest score of 58.75 increased to 91.25 in the posttest, indicating a statistically significant gain. These findings suggest that incorporating short stories as a learning medium can effectively enhance students’ comprehension skills. The narrative form of short stories actively engages learners and provides meaningful context for language acquisition. The discussion emphasises the potential of short stories as an alternative teaching medium to increase motivation, involvement, and literacy development among elementary students. Furthermore, this study underlines the importance of integrating diverse and interactive media in literacy education to address different learning needs and preferences. Therefore, educators are encouraged to utilise creative approaches such as short stories to improve reading comprehension outcomes in elementary education.